Social Influence and Elderly Smartwatch Adoption: A Conceptual Model - Irina CRISTESCU; Dragoș-Daniel IORDACHE; Ovidiu BICA (Communications of International Proceedings, 2021)
Nowadays, smartwatches have become popular among the wearable gadgets. In the context of a fast-aging population smartwatches respond also to healthcare and assistance needs, which is an advantage when dealing with the older population. Thus, the importance to identify the determinants of smartwatch adoption. The aim of this study is to propose a conceptual model for adopting smartwatches by older adults. The proposed model is based on the TAM model. The proposed factors are defined, and the corresponding hypotheses are formulated. Also, the analytical procedures that will be used in future work to test the conceptual model are presented.
Keywords: Smart wearables; smartwatch adoption; technology acceptance model; TAM; social influence.